HUBUNGAN PENDAPATAN DAN PENGETAHUAN KEPALA KELUARGA DENGAN KETERSEDIAAN JAMBAN SEHAT DI DESA GUNUNG MERLAWAN KECAMATAN TIGANDERKET KABUPATEN KARO TAHUN 2019 - Bunga Mari Sembiring; Desi Veronika; Fithri Handayani Lubis (Jurnal Penelitian Kesmasy, 2019)
To improve public health in the form of disease prevention, and health recovery by the government and society is the development of basic sanitation. Any of them has access to basic sanitation that is healthy latrines. The purpose of this study was to determine the relationship of income and knowledge of family heads with the availability of healthy latrines . The method of this study used observational analytics with a cross sectional study design. The population in this study was the family Head of the gunung merlawan village as much as 60 households in Tiganderket District Karo Regency. Samples were taken according to the number of samples of 60 households with 230 inhabitants. with this sampling technique is total sampling. Statistical tests using the chi square test using SPSS 20. The results of the study showed that there was a relationship between the level of income of family heads with the availability of family latrines. And that there is a relationship of knowledge with the availability of healthy latrines. It is recommended to health officer in the working area of Puskesmas Tiga Nderket and the Head of Gunung Merlawan village to increase their role in counseling the community in the use of healthy latrines in Gunung Merlawan village, Tiganderket .